An Exploratory Study of Indonesian Teachers’ Digital Literacy Competences - Soepriyanti, Henny; Waluyo, Untung; Sujana, I Made; Fitriana, Eka (Technium Social Sciences Journal, 2022)
This study aims to reveal how high school teachers adjust to the demand of utilizing digital literacy skills in two selected areas of the Lombok Island, Indonesia. The study sought to get deep understanding of how high school teachers developed their digital literacy competences and kept up with the demand of online teaching of English during the pandemic time. The study also sought to identify problems pertaining to the utilization of digital literacy in the pandemic time. The study employed a qualitative method with multiple-case design. A purposive Sampling technique was used to determine the key informants for the study. The data were obtained from various sources, which included interviews, observations and document studies. The process of data analysis encompassed data reduction, data presentation, and conclusion drawing. This was done through triangulation of data iteratively. The data were then analyzed thematically. The study yields that teachers in the two selected research areas acquired varying degrees of digital literacy competences due to different goal-setting, interests, knowledge and skills. A number of problems pertaining to teachers’ differing competences in digital literacy were identified, i.e. (1) lack of internet access (2) the absence of professional development, (3) and institutional support system. All of these problems were intertwined in nature. The study concludes that a professional development program needs to be devised for the participants to improve their performance and competence in utilizing digital literacy.